Pojęcie zdolności kredytowej - Janiak, Andrzej (Wydział Prawa i Administracji UAM, 1986)
There was a principle adopted upon reforming banking and credit system in Poland, that a sine qua non condition to open a credit for the borrower is his capacity to raise a credit. Yet, legal acts introducing the economic reform failed to precise the contents of the notion "capacity to raise a credit". In fact, both in literaturę and in practice divergent opinions can be encountered upon discussing that issue. The tank of the present article is to explicate the essence of the notion on the grounds of valid credit laws in Poland. The author shares the opinion that a normative category of capacity to raise a credit has to be derived from banking law regulations. Provisions of that statute prove that the capacity to raise a credit is to be understood as a credited party's solvency in the respect of repayment of a drawn credit. Opposing the attempts of different concepts of capacity to raise a credit to extend the notion's range, the author indicates at the same time that the capacity to raise a credit as the solvency in the respect of a drawn credit is the basic but not the sole- as it is sometimes advocated- riterion of opening credits by banks. In the Polish economy the interest rates are not shaped along the suppily- -demand formula and do not express the generation of effectivness in economy. Maintaining limits to crediting action requires thus a peculiar banking control of credits. The very criterion of capacity to raise a credit cannot be sufficient to select credit applicants. The additional criteria would be necessary. They are currently established by the Diet in its annual foundations of monetary-credit
A Notion of Capacity to Draw a Credit